PRONE POSITION IN ACUTE RESPIRATORY DISTRESS SYNDROME AFTER CORONAVIRUS INFECTION - Mafalda Mota; Luís Sousa; Isabel Bico; Maria do Céu Marques (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Introduction: The new coronavirus infection appeared in China in December 2019, it spread rapidly throughout the world, and was considered a pandemic by the World Health Organization in March 2020. This infection can cause pneumonia requiring hospitalization in intensive care units. The prone position is one of the interventions that can help in the treatment of acute respiratory distress syndrome in these people. Objective: to identify the effects of the prone position in the treatment of patients with acute respiratory distress syndrome caused by the corona virus. Method: integrative literature review conducted in May 2020. The following databases were used for data collection: SCOPUS, MEDLINE, and Google Scholar. Inclusion and exclusion criteria were applied. Results: Of the 241 articles identified, 13 articles were selected, all published in 2020. The data was synthesized in 3 main subjects, indications, frequency of position changing and duration, and lastly, the effects of the prone position. Conclusions: The prone position in this context, helps improve ventilatory and blood gas parameters, dyspnea symptoms, facilitates recovery, and consequently, early discharge, reduces hospitalization days and reduces mortality at 28 and 90 days.